Green marketing impact on youth purchasing: Bangladesh district-wise study on consumer intentions - Tamim, Md. S. R.; Lipe Akter (goodwood publishing, 2024)
Purpose: In this comprehensive project, the primary objectives revolve around crafting an intricate model and delving into the intricate dynamics among key elements: green product (GPR), green price (GPI), green place (GPL), green promotion (GPO), and green perceived value (GPV), and their impact on customer purchase intention (CPI). Research Methodology: This study was descriptive, and a convenience sampling technique was used to collect data. Primary and secondary data were used in this study. The empirical foundation is grounded in data collected from a robust sample of 235 young consumers. Rigorous analysis, employing SPSS version 26's descriptive, reliability, correlation, and multiple regression tools, was performed to extract meaningful insights. Results: The findings reveal a positive correlation between green product (GPR), green price (GPI), green place (GPL), green promotion (GPO), and green perceived value (GPV) and customer purchase intention. Limitations: It is worth noting that the study's demographic concentration in the Cumilla, Dhaka, and Chittagong districts may limit its generalizability to young consumers in Bangladesh. Contribution: This study offers valuable recommendations for businesses, NGOs, governments, and other stakeholders to bolster their competitive positions and contribute to a sustainable environment. Novelty: These insights underscore the need for nuanced strategies tailored to the diverse landscape of consumer behavior in Bangladesh.